The role of traditional institutions in implementing the empowerment policy of Oetulu village, Musi district, Timor Tengah Utara regency - Yohanes K. Olin; Petrus Kase; Hendrik Toda (Goodwood Publishing, 2021)
Purpose: This study aimed to determine the role of indigenous institutions in implementing the Oetulu village Empowerment Policy of Musi district of North Central Timor regency. Research methodology: The research method in this study was a descriptive research method with a qualitative approach. This study used policy implementation theory models from Donald Van Meter and Carl E. Van Horn (1975)). Results: Six variables affect the implementation, namely: First, policy standards in the form of rules related to indigenous institutions in Oetulu village have been flawed at the formulation stage. Second, the human resources of Oetulu village indigenous institutions are not utilized by the Village Government. Third, communication between organizations and strengthening activities is still not effective. Fourth, the implementing agent has an open level of communication both vertically and horizontally, but this communication is constrained at the vertical level. Fifth, economic conditions in the jurisdiction or implementing organization are not enough to support the implementation of the policy and. Sixth, the disposition of the implementer. Limitations: This research only discusses the role of indigenous institutions in implementing the community empowerment policy of Oetulu village, Musi district of North Central Timor regency. Contribution: This research becomes scientific information for public administration science.